Calculation of temperature fields in ampoules under the radiation treatment by electrons with energy 10 MeV - Bakai, A.S.; Tanatarov, L.V.; Gonchar, V.Yu.; Sergiyeva, G.G. (Вопросы атомной науки и техники, 2005)
To obtain the temperature fields in ampoules under the radiation treatment we use the one-dimensional equations of the thermal conductivity on the coordinates along the axis which is congruent with the direction of the beam. The results of the calculations of temperature fields within the ampoule are discussed for two cases: for the ampoule with the molten fluorides mix between three tested Hastelloy specimens (in section 1); and for the ampoule with exhalations of ftuorides salts (in section 2). These two situations are differed as in the energy losses of electron beam, as well in the mechanism of heat transport, that leads to essentially different temperature fields inside of the ampoule. It is shown that for ampoule with fluoride salts exhalations the stationary temperatures strongly depend from heat transport mechanisms and from layers thickness, that leads to conclusion about necessity to take into account both mechanisms of heat transport (thermal radiation and thermal conductivity) simultaneously. При розрахунках температурних полей в ампулі під випромінюванням електронами нами використовувались одновимірні рівняння теплопровідності із вісью х, яка збігається із напрямком потоку електронів. Одержані коордінатні залежності температури для двох випадків: 1) для ампули із с розплавом солей флюориду між випробуваними зразками Хастелоя; 2) для ампули із парами солей флюориду між шарами ампули.. Показано, що у другому випадку сталий розподіл температури істотно залежить від механизму переносу тепла і товщини шарів, що дозволяє зробити висновок про необхідність одночасно брати до уваги обидва механізми переносу тепла (теплове випромінювання і теплопровідніть шарів). Для вычисления температурных полей в ампуле под облучением электронами нами использовались одномерные уравнения теплопроводности с осью х, совпадающей с направлением потока электронов. Получены координатные зависимости температуры для двух случаев: 1) для ампулы с расплавом солей флюорида между испытуемыми образцами Хастеллоя; 2) для ампулы с парами солей флюорида между образцами Хастеллоя. Показано, что во втором случае установившееся распределение температуры существенно зависит от механизма переноса тепла и от толщины слоев, что позволяет сделать вывод о необходимости принимать во внимание оба механизма переноса тепла одновременно( тепловое излучение и теплопроводность слоев).